ELEMEN-ELEMEN “SOCIAL APPONOMICS” GARUDA INDONESIA SEBAGAI UPAYA UNTUK MENINGKATKAN POTENSI E-COMMERCE DI ERA EKONOMI DIGITAL - Purwitasari, Ira; Setiawan, A Judhie; Muktaf, Zein Muffarih (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka Palembang, 2019)
The purpose of this study is to determine the elements of Garuda Indonesia's Social Apponomics as an effort to increase the potential of e-commerce. The study was conducted at the 1st Floor Management Building, Garuda City, PT Garuda Indonesia (Persero) Tbk, Soekarno Hatta International Airport, Tangerang. The type of research used is descriptive with a qualitative approach. Techniques used in data collection include: a) Primary Data, which consists of in-depth interviews, b) Secondary Data taken from books, journals, articles, and previous research correlated to this research. The technique of determining the informants (informants) used was purposive sampling technique. The results of this study indicates that Garuda Indonesia has implemented Social Apponomics practices in the digital economy era. This is indicated by the founding of three elements forming Social Apponomics in Garuda Indonesia, namely (1) Social Media; (2) Community-based Marketing; and (3) Tailored Applications. Another finding from this study is that the Garuda Indonesia Brand is still the brand that has the highest Brand Advocacy Ratio index score in Indonesia compared to its competitors with a score of 0.81.